About causes for the insular localization of beech forests near eastern limit of the range - Melnyk, V.I. (Reports of the National Academy of Sciences of Ukraine, 2022)
Beech forests in uncial natural heritage of Europe. Beech forests of Wolhynian-Podolian Upland, located near the Eastern limite of Fagus sylvatica L. range, are especial valuable. They could be interesting for forestry since they differ by the high, genetically determined productivity, frost and drought resistant. Some rare species of the flora of beech forests of Wolhynian-Podolian Upland are listed in the Red Data Book of Ukraine. As uncial cente of biological diversity lowland beech forest are included to Green Data Book of Ukraine. An actual problem in the development of a scientific foundation of the conservation of beech forests of Wolhynian-Podolian Upland under the global warming condition. Controversial and one of the most interesting in theoretical sense is the question about the causes for the insular localization of beech forests near Eastern limit of range in Wolhynian-Podolian Upland. Insular localization of beech forests near Eastern limit of the range in Wolhynian-Podolian Upland is connected with the inconsistent atmospheric and soil humidity condition to the ecological needs of beech seedlings. In forest-steppe zone of Ukraine surfaces of all types of soils even often short droughts become deprived of moisture necessary for seedlings growth and development. In the summer period there is a loss of moisture and, in that regard seedlings elimination. Only in specific conditions of atmospheric and soil humidity on the most elevated areas of relief, where on average per year are falls on 90-100 mm or 15-20 % of precipitation more than in the surrounding areas, microclimatic conditions are favorable for continuous growth and development for beech seedlings. Only in such conditions are possible continuous change of the generation of beech threes and relatively existents of the beech forests near Eastern limit of the range. So far as, from 3-5-age the systems of additional roots in Fagus sylvatica are formed continuous, the zone of soil nourishment is not limited to surface layer of soil. Planted trees of that age are grown well in edaphotopes, where existence of beech seedlings without watering is impossible. In this connection, unlike natural beech forests, beech cultures are grown in large range of habitats in Wolhynian-Podolian Upland. Given the value of gene pull of Fagus sylvatica near Eastern limit of the range, it is advisable to increase the area of beech forest cultures within and beyond it natural range.